2017
DOI: 10.1094/pdis-10-16-1517-re
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Native Populations of the Laurel Wilt Pathogen,Raffaelea lauricola, in Taiwan and Japan and the Introduced Population in the United States

Abstract: Laurel wilt is a vascular wilt disease caused by Raffaelea lauricola, a mycangial symbiont of an ambrosia beetle, Xyleborus glabratus. The fungus and vector are native to Asia but were apparently introduced to the Savannah, GA, area 15 or more years ago. Laurel wilt has caused widespread mortality on redbay (Persea borbonia) and other members of the Lauraceae in the southeastern United States, and the pathogen and vector have spread as far as Texas. Although believed to be a single introduction, there has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 66 publications
6
17
1
Order By: Relevance
“…Cryptic sex was hypothesized for Raffaelea lauricicola T.C. Harr., Fraedrich, & Aghayeva, the mycangial symbiont of Xyleborus glabratus Eichhoff., but ascomata were not identified (Wuest et al 2017). …”
Section: R a F Tmentioning
confidence: 99%
“…Cryptic sex was hypothesized for Raffaelea lauricicola T.C. Harr., Fraedrich, & Aghayeva, the mycangial symbiont of Xyleborus glabratus Eichhoff., but ascomata were not identified (Wuest et al 2017). …”
Section: R a F Tmentioning
confidence: 99%
“…Primers have been previously developed that amplify portions of the MAT1-1 genes (MAT1-1-3) [17] and MAT1-2 genes (MAT1-2-1) [20].…”
Section: Mating-type Assaymentioning
confidence: 99%
“…Recently, this hypothesis was investigated with genetic markers in R. lauricola. Wuest et al [17] used two simple sequence repeat (SSR), a single nucleotide polymorphism (SNP) and mating type markers with isolates from the USA, Japan and Taiwan, whereas Hughes et al [5] used amplified fragment length polymorphism (AFLP) and SSR markers to examine isolates recovered early in the USA epidemic. Although the studies used a limited number of markers or isolates, Hughes et al [5] and Wuest et al [17] suggested that a single introduction of the pathogen had occurred in the USA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although R. lauricola has been detected in X. glabratus in Asia (Dreaden et al 2019;Harrington et al 2011), laurel wilt disease has not been found in the US prior to the appearance of the X. glabratus (Ploetz et al 2013). R. lauricola populations are quite diverse in East Asia, but the pathogen and its vector seem to be clonal in the US (Cognato et al 2019;Dreaden et al 2019;Hughes et al 2017;Wuest et al 2017). This suggests that both were introduced in a single event, possibly being carried to the port of entry in untreated packing material Ploetz et al 2017).…”
Section: Introductionmentioning
confidence: 99%